All-cause Mortality in Knee and Hip Osteoarthritis and Rheumatoid Arthritis. Issue 4 (July 2016) - Turkiewicz, Aleksandra; Neogi, Tuhina; Björk, Jonas; Peat, George; Englund, Martin
Abstract : Background: While increased mortality in rheumatoid arthritis (RA) is well established, there is conflicting evidence on the association between osteoarthritis (OA) and mortality. Our aim was to estimate all-cause mortality in Swedish patients with RA and OA compared with the general population. Methods: Cohort study of the population of Skåne region, Sweden (1.3 million), based on physicians' diagnostic codes in a mandatory register covering all health care. We included all subjects aged ≥45 years who between 1998 and 2012 consulted any physician at least once. We identified those who received a diagnosis of RA, knee OA, or hip OA. We followed all subjects until death, relocation outside Skåne region, or end of 2013, and analyzed data using Cox proportional hazard regression with attained age as time scale. Results: We identified 8, 067 patients with RA, 51, 939 with knee OA and 29, 442 with hip OA among 524, 136 in the population aged ≥45 years. The mortality rates adjusted for sex, socioeconomic status, and comorbidities were elevated for RA, hazard ratio 1.86 (95% confidence interval = 1.78, 1.94) but not in knee or hip OA compared with the general population seeking health care, hazard ratio 0.87 (0.85, 0.89) and 0.90 (0.87, 0.92), respectively. Extensive sensitivity analyses supported the conclusion of no increased mortality in OA. Conclusions: In Sweden, RA is associated with about doubled mortality rate, but we found no increased mortality in patients with knee and hip OA. Possible selection of those seeking physician care for knee or hip pain and/or OA management in health care are plausible explanations. Abstract : Supplemental Digital Content is available in the text.